2001
DOI: 10.1046/j.1440-1827.2001.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Classic type of Kaposi's sarcoma and human herpesvirus 8 infection in Xinjiang, China

Abstract: We report 17 cases of the classic type of Kaposi's sarcoma in Xinjiang, which is located in the north-western area of China surrounded by Mongolia in the east, Russia in the north and Kazakhstan in the west. Fifteen of the patients were of the Uygur people. All patients were male and did not have acquired immunodeficiency syndrome. Most of the lesions were found in the lower and/or upper extremities, with 16 patients showing multiple lesions. Immunohistochemical examination of the lesions revealed that human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 32 publications
(81 reference statements)
5
59
0
2
Order By: Relevance
“…Very little is known about KSHV infection in China even though EBV infection was found to be ubiquitous. There were only two reported studies in China; the study by Dilnur et al [45] found that KSHV was associated with KS in China. The study by Du et al [46] in the outskirt of China in the Xinjiang autonomy region, where there is a high incidence of HIV-1 infection, showed that there was a high HHV-8 infection rate.…”
Section: Human Herpesvirus and Ksmentioning
confidence: 99%
“…Very little is known about KSHV infection in China even though EBV infection was found to be ubiquitous. There were only two reported studies in China; the study by Dilnur et al [45] found that KSHV was associated with KS in China. The study by Du et al [46] in the outskirt of China in the Xinjiang autonomy region, where there is a high incidence of HIV-1 infection, showed that there was a high HHV-8 infection rate.…”
Section: Human Herpesvirus and Ksmentioning
confidence: 99%
“…However, regional differences have been reported. In Asia, geographic pockets with lower or higher (1.4-46.6%) prevalences were found Dilnur et al, 2001;Satoh et al, 2001]. In Europe, frequencies from 3.0 to 35% have been reported [Gambus et al, 2001;Preiser et al, 2001;Santarelli et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that our patient is of sub-Saharan African origin is rather unusual for classical KS. Nevertheless, occurrence of classical KS in non-Mediterranean countries such as Peru and China has been documented [7,8]. The striking geographical variation in the incidence of classical KS and African-endemic KS points to a role for environmental factors.…”
Section: Iroezindu and Achusi Classical Kaposi's Sarcoma In Nigeriamentioning
confidence: 99%